(3cJGH aj GdHGgs - (3bSWG Hf dhbG GdHYdHcis; (3GdgQhj , eMeO Hf jhSa GdWHjH,J (B924 (3g` ? s ((3ejNGFjd Hf jhMfG Gdedci GdeJWHH s)
(3ChdgG (B:s
(3GdHGH GdChd (B: (3HeGPG jJe GSJYeGd GdHGg hjbhi GdEfSGf Ydi GdEcKGQ efg s
(3BNQgG (B:s
(3HeG jMOK ef GdEeJfGY ef GdHGg ` GLJeGY GdQWhHGJ ai GdHOf hGNJfGb GdHNGQGJ GdeJhdOI YfgG ajg s
(3QJHI Ydi GKfjf hYTQjf HGHkGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B134s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdChd (B- (3U (B32 s
Keywords: (3GdWHs